2021
DOI: 10.1681/asn.2020081143
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleus RNA Sequencing Identifies New Classes of Proximal Tubular Epithelial Cells in Kidney Fibrosis

Abstract: Background: Proximal tubular cells (PTCs) are the most abundant cell type in the kidney. PTCs are central to normal kidney function and to regeneration versus organ fibrosis following injury. This study used single-nucleus RNA sequencing (snRNA-seq) to describe the phenotype of PTCs in renal fibrosis. Methods: Kidneys were harvested from naïve mice and from mice with renal fibrosis induced by chronic aristolochic acid administration. Nuclei were isolated using Nuclei EZ Lysis buffer. Libraries were prepared o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 56 publications
6
40
0
Order By: Relevance
“…The histological assessment of deposited collagen and extracellular matrix protein confirmed the expression data of the genes. Of note, renal fibrosis arises after an insult, whereas resident kidney fibroblasts and cells of hematopoietic origin differentiate into myofibroblasts [ 21 , 22 , 23 ]. Myofibroblasts acquire a contractile/proliferative phenotype upon activation by profibrotic factors and become principal kidney collagen-producing cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The histological assessment of deposited collagen and extracellular matrix protein confirmed the expression data of the genes. Of note, renal fibrosis arises after an insult, whereas resident kidney fibroblasts and cells of hematopoietic origin differentiate into myofibroblasts [ 21 , 22 , 23 ]. Myofibroblasts acquire a contractile/proliferative phenotype upon activation by profibrotic factors and become principal kidney collagen-producing cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, injured proximal tubule epithelial cells are still considered important drivers of kidney injury and fibrosis, as e.g., also recently demonstrated by scRNA-seq studies in mouse models of acute kidney injury ( 21 , 22 ). snRNA-seq in a fibrosis mouse model of chronic aristolochic acid administration identified novel classes of proximal tubular cells associated with kidney fibrosis ( 23 ). A scRNA-seq study in kidneys of patients with IgA nephropathy identified a transitional cell type among tubular intercalated cells with fibrosis signatures, suggesting an adverse outcome with interstitial fibrosis ( 24 ).…”
Section: Initiation Of Kidney Fibrosismentioning
confidence: 99%
“…Previous studies 30,63,[67][68][69][70] revealed that failed TEC repair elicits pro-fibrotic phenotypes promoting AKIto-CKD progression. Our analysis predicted increased intercellular communications in kidney fibrosis and corroborated the active role of TECs in the fibroblast activation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in understanding the molecular and cellular landscapes of normal and diseased human and murine kidney 30,49,[61][62][63][64][65] , renal quiescent and activated fibroblasts remain an elusive population. Kuppe et al 49 used spatial transcriptomics and genetic fate tracing to examine human CKD and murine UUO induced renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation